Characteristics of the water column of the North Basin of Lake Lugano, Switzerland, at different time points - depth of oxygen depletion, fluxes to the redox transition zone, primary production, nitrate isotope effects - Jana Tischer; Jakob Zopfi; Fabio Lepori; Guangyi Su; Elena Giglio; Claudia Frey; Moritz F Lehmann (PANGAEA, 2025)
We investigated the water column of the meromictic Lake Lugano North Basin, Switzerland, during 12 sampling campaigns between 2015 and 2018. The dataset contains parameters specific to the water column during each sampling campaign: compound fluxes to the redox transition zone and calculated consumption rates as well as N and O isotope effects of nitrate, and depth of oxygen depletion. In addition, we show the gross primary production of carbon during the month of sampling.